Recruitment and Selection : Strategies for Workforce Planning & Assessment / Carrie A. Picardi - Picardi, Carrie A.
The workforce is changing and talent management is more important than ever. Recruitment and Selection: Strategies for Workforce Planning & Assessment unpacks best practices for designing, implementing, and evaluating strategies for hiring the right people. Using a proven job analysis framework, author Carrie A. Picardi uses her academic and industry experience to teach students how to assess candidates in an accurate, legal, and ethical manner. With clarity and relevance, this book truly bridges theory and concept with practice in an engaging manner and will benefit students who need to hit